Nacre‐Inspired, Efficient, and Multifunctional Soft Magnetic Composites by Cold Sintering Design. Issue 7 (13th January 2022) - Zhou, Tingchuan; Liu, Ying; Li, Jun; Wang, Renquan; Du, Jiao; Ye, Jinwen; Chen, Hongxing; Li, Wangchang; Wu, Chen; Zhang, Huaiwu
Abstract : Nacre‐mimetics hold great promise as integration of structure and function. Various techniques have been proposed to prepare nacre‐inspired materials, but in most cases, organic materials are usually used that decrease high‐temperature stability. Factually, efficient synthesis of nacre‐like high‐performance soft magnetic composites (SMCs) with good thermal stability is still challenging. Herein, a novel and simple strategy is reported on designing nacre‐like SMCs by cold sintering of ferrite‐coated alloy flakes with the absence of polymers. By selecting NH4 HCO3 aqueous solution as transport solvent, a highly ordered nacre‐like structure and enhanced densification with large electrical resistivities and strong interfacial bonding are successfully achieved, which are superior to the cold‐sintered composites using water as transport solvent as well as the hot‐pressed composites based on alloy flakes and epoxy resin. The resultant composites illustrate large density (≈6.286 g cm −3 ) and electrical resistivity (≈3.9 × 10 5  Ω cm), allowing remarkable flexural strength (≈46.5 MPa), high permeability ( μ ′ = ≈107.3 at f  = 10 MHz), together with low tan δ μ (≈0.09 at f  = 10 MHz) and P cv (≈183.6 kW m −3 at 50 mT/100 kHz), which show great potential in high‐frequency power electronic and electrical systems. The synthesis strategy sheds light on designing other nacre‐like materials or developing new metal−ceramic composites. Abstract : A novel and simple strategy is developed for nacre‐like soft magnetic composites design by cold sintering of ferrite‐coated alloy flakes using NH4 HCO3 aqueous solution as transport solvent. The resultant materials exhibit nacre‐like structures with high densification, large electrical resistivities, and strong interfacial bonding, allowing remarkable magnetic and mechanical properties, which have great potential applications in high‐frequency power conversions.